Mystery cults in visual representation in Graeco-Roman antiquity - Belayche, Nicole; Belayche, Nicole; Massa, Francesco; Massa, Francesco (Religions in the Graeco-Roman world, 2020)
Intro -- Contents -- Figures -- Notes on Contributors -- 1 Mystery Cults and Visual Language in Graeco-Roman Antiquity: An Introduction -- Part 1 Do Images Depict Mystery Cults, and If So, How? -- Introduction to Part 1 -- 2 Comment figurer l'ineffable, comment lire les images ? -- 3 Le phallus qui cache le mystère ? Les images dionysiaques dans les décors romains : à propos d'une fresque de la Domus Transitoria -- 4 Échos de la Télétè dionysiaque dans la mosaïque romaine tardive -- Part 2 Historiography and Images of Mystery Cults -- Introduction to Part 2 -- 5 'The Seven Grades of Mithraism', or How to Build a Religion -- 6 Les mystères isiaques et leurs expressions figurées. Des exégèses modernes aux allusions antiques -- Part 3 Depicting Objects to Signify Mystery Cults -- Introduction to Part 3 -- 7 The Liknon and the Bundle: Does the Ritual 'Initiatory' Object Make the Mystery? -- 8 The Cista, a Hallmark of Mater Magna's Mysteries in the Roman World? -- Selected Bibliography -- Index of Ancient Authors -- Index of Inscriptions (in corpora) -- General Index.